INNOVATIVE MEASURES OF PROVIDING YOUTH EMPLOYMENT (International Conference on Modern Science and Scientific Studies, 2025)
In this article, it is stated that the state's innovative policy of ensuring youth employment in Uzbekistan has shown its positive results in social life over the years.